2004
DOI: 10.1002/ejic.200400214
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom‐Substituted Group 4 Bis(indenyl)metallocenes

Abstract: The synthesis, characterization and applications of heteroatom‐substituted group 4 bis(indenyl)metallocene complexes is reviewed. In recent years, an increasing number of group 4 metallocenes with electronically modified cyclopentadienyl ligands have been reported with, in some cases, considerably altered catalytic properties. This microreview focuses on bis(indenyl) complexes of titanium, zirconium and hafnium that contain nitrogen, oxygen and sulfur atoms directly bonded to the five‐ or six‐membered rings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(25 citation statements)
references
References 136 publications
0
25
0
Order By: Relevance
“…Table 3 shows polymerisation data for the 5a-c complexes under co-polymerisation conditions using ethylene and 1-hexene, with MAO as co-activator. It shows that all three complexes 5a-c have a low polymerisation activity compared with previously published structures [14,18]. Molecular weights of the hexene-ethylene copolymers are markedly high in the case of 5a with M w = 919,000 and much lower with 5c, M w = 65,500.…”
Section: Molecular Structure By X-ray Analysismentioning
confidence: 68%
See 2 more Smart Citations
“…Table 3 shows polymerisation data for the 5a-c complexes under co-polymerisation conditions using ethylene and 1-hexene, with MAO as co-activator. It shows that all three complexes 5a-c have a low polymerisation activity compared with previously published structures [14,18]. Molecular weights of the hexene-ethylene copolymers are markedly high in the case of 5a with M w = 919,000 and much lower with 5c, M w = 65,500.…”
Section: Molecular Structure By X-ray Analysismentioning
confidence: 68%
“…There are 7 XRD structures of previously published siloxy-substituted-bis-zirconocenes that can be found in the CCDC database [14]. They are all indenyl or tetra-hydroindenyl type zirconocenes with one siloxy substituent in the 5-ring and having an ethylene bridged structure.…”
Section: Molecular Structure By X-ray Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of amino-functionalized cyclopentadienes [23,24] and indenes [23][24][25][26] through reaction of the cyclopentenone (indanone) with secondary amines and their use for synthesis of the transition metal complexes [22][23][24][25][26] was the subject of several studies. However this is the first example of applying this method to the synthesis of the cyclopentadienyl-based framework containing both tertiary amino and carboxylic ester groups.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Recently, e.g., Halterman, [12,13] Takahashi et al, [14] and Takai and co-workers [15] have reported efficient metal-mediated or metal-catalyzed methods for preparation of new indenyl frameworks.…”
Section: Introductionmentioning
confidence: 99%